Success Assesment of Patients Rehabilitated with Removable Prosthesis - Valverde DDS, Anabelle; Fernández DDS, MSc, Otton; Vargas DDS, MSc, Tatiana (Odovtos - International Journal of Dental Sciences, 2016)
The aim of this study is to determine the level of patient satisfaction with dentures rehabilitated a the School of Dentistry, from 2011 to 2013, using the OHIP-49 instrument, OHIP-19 edent and WHO criteria for oral health surveys. Materials and Methods: A previously validated survey instrument was applied by telephone to a sample of 152 patients from the University of Costa Rica. Correlation coefficients and logistic regression were carried out in order to correlate socio-demographic characteristics with general and specific satisfaction levels. Results: the general satisfaction generated by the patient on a scale of 1 to 10 was 9.3. Satisfaction derived from specific categories was 8.54, with factors such as mastication and daily use without pain being the less satisfactory. The lower dentures were the least accepted in factors such as mastication and free use of pain. By applying the correlation coefficient, high and positive relationship was found related to mastication. Logistic regression found that patients older than 56, who do not exercise and drink alcohol, are more likely to generate lower levels of satisfaction. Conclusions: The percentage of overall satisfaction of patients rehabilitated with dentures was above 85%. Less satisfactory qualities were mastication and daily use without the presence of pain.